Métodos para iniciação de crianças ao violoncelo: leituras e usos - um estudo na região sul do Brasil - Reys, Maria Cristiane Deltregia (2011)
This dissertation binds to the line of research Education and Arts LP4, from the Graduate Program in Education of the Federal University of Santa Maria/RS, and to the Group of studies FAPEM (CNPq): Training, action and research in Music Education. The research objective was to analyze readings and usages of cello teacher, active in the southern region of Brazil, about methods used in the initiation of children. To this end, it was necessary a review and a brief analysis of the methods, as well as investigates how these books are adapted and supplemented in different realities. The study had the theoretical contribution of Roger Chartier referential (1997, 1999, 2002a and 2002b), considering the musical text a reading object constituted of materiality and liable to interpretation. For the realization of the work, the musical methods were studied while textbooks for instrumental teaching, as well as aspects relating to the repertory and musical development in the stage of initiation. For this, it was sought to establish a dialogue with the authors of the areas of Education and Music, in interfaces with Music Education. In this sense, were used as benchmarks studies of authors such as Anne-Marie Chartier (2007) and Alain Choppin (2004), in the area of Education; Garbosa (2003, 2009), Souza (1994), Penna (2008), Torres (2009), França and Swanwick (2002), Pleeth (1982) and Maciente (2008) in the area of Music, among others. Methodologically, the research, of a qualitative nature, had as its main data sourced the talks of cello teachers, considering their readings and experiences in the use of methods. From the study, it was noted that some methods are chosen as the basis for the work of initiation, however, the proposals from authors do not paralyze the practices of the teachers, there is freedom in reading and great diversity of uses. The methods are chosen and supplemented, in accordance with the needs of the community of readers cellists. The results also point to the influence of textbook in the dissemination of musical education proposals that prioritize the making music at the expense of an education focused on technique and on the performance.